FRP-Confined Concrete Columns: A New Procedure for Evaluating the Performance of Square and Circular Sections. (11th October 2018) - Fossetti, Marinella; Basone, Francesco; D'Arenzo, Giuseppe; Macaluso, Giuseppe; Siciliano, Alfio Francesco
Abstract : In the last few decades, the upgrading of existing reinforced concrete columns with the use of FRP jackets has met with increasing interest for its effectiveness and ease of application. The use of these kinds of jackets ensures an improvement of the affected column in terms of strength and ductility; however, the prediction of behavior of columns wrapped with FRP jackets is still an open question because of the many parameters that influence the effectiveness of the upgrading technique, and several semiempirical models are proposed. Because these models are often only applicable to specific cases, in this paper, a generalized criterion for the determination of the increase in strength, in ductility, and in dissipated energy for varying corner radius ratios of the cross section and fiber volumetric ratios is shown. Numerical results using a finite element analysis, calibrated on the basis of experimental data available in the literature, are carried out to calibrate the new analytical models. A comparison with some available models confirms the reliability of the proposed procedure.